Association Between Lactation and Postpartum Blood Pressure in Women with Preeclampsia. Issue 2 (March 2019) - Burgess, Adriane; McDowell, Wendy; Ebersold, Stacie
Abstract: Purpose: Preeclampsia affects 3% to 8% of all pregnancies. There are two distinct subtypes; early- (<34 weeks) and late-onset (≥34 weeks). Each subtype is associated with increased risk of cardiovascular disease. Lactation has been shown to improve cardiovascular outcomes. The purpose of this study was to describe lactation practices among women with each subtype of preeclampsia and determine the association between lactation and blood pressure at the initial postpartum visit. Study Design and Methods: This retrospective cohort study included 246 subjects; 120 early- and 126 with late-onset preeclampsia who gave birth to live singleton newborns at a large suburban tertiary referral center in south central Pennsylvania between January 2012 and June 2016. Electronic health records were reviewed and data abstracted. Univariate and bivariate analyses were conducted. Results: There was a significant difference in breastfeeding intent ( p = .004) as well as rate of breastfeeding at maternal hospital discharge ( p < .001) by preeclampsia subtype. However, there was no difference in rate of breastfeeding at the initial postpartum visit ( p = .21) between subtypes. There was a significant difference in systolic ( p = .03) and diastolic ( p = .04) blood pressure between those breastfeeding and those who were not breastfeeding at the initial postpartum visit. Clinical Implications: Healthcare providers should provide women with preeclampsia clear and consistent messaging about importance of breastfeeding during pregnancy and the postpartum period on its association with improved neonatal outcomes, and specifically education on the cardioprotective benefit of sustained lactogenesis. Abstract : Women who have preeclampsia are at increased risk for cardiovascular disease later in life. Breastfeeding has been shown to be cardioprotective. In this study of women who had preeclampsia, there was a significant difference in systolic and diastolic blood pressure between those who were breastfeeding and those who were not at the initial postpartum visit. Women who have preeclampsia need information about potential benefits of breastfeeding as well as their risk of cardiovascular disease as they get older.